Prevalence of colon lesions diagnosed by videocolonoscopy from 2019 to 2021 (Research, Society and Development, 2023)
Colonoscopy is a crucial procedure for both the diagnosis and treatment of a variety of conditions affecting the rectum, colon, and part of the terminal ileum, including polyps, inflammatory bowel diseases, and colorectal cancer. Its indications encompass colorectal cancer screening, the investigation of abnormalities detected in imaging studies, the assessment of symptomatic patients (such as those with lower gastrointestinal bleeding and chronic diarrhea), as well as the monitoring of previously diagnosed intestinal conditions. Moreover, colonoscopy allows for therapeutic interventions, such as biopsies, polypectomies, management of bleeding, dilation, or stent placement in cases of symptomatic colonic strictures, marking of lesions for future surgical resection, among others. The aim of this study was to analyze the prevalence of colonic lesions identified through videocolonoscopy from 2019 to 2021. To achieve this, the reports of patients who underwent videocolonoscopy at a clinic in Aracaju during this period were reviewed. According to the research findings, polyps were the most common findings in colonoscopies, with a higher prevalence in the transverse colon, sigmoid colon, and rectum. These findings suggest that flexible sigmoidoscopy, due to its minimally invasive nature and easy accessibility, may play a significant role in detecting polyps during colorectal cancer screening, particularly in distal lesions.